Use of Digital Games in Mathematics Classes: A Systematic Literature Review - Kanobel, María Cristina (2022)
This article presents the main findings of a systematic literature review of the inclusion of digital games in Mathematics teaching proposals. The documentary search has been carried out from the triangulation of sources included in the Scopus and Dialnet databases, corresponding to the period from January 2020 to February 2022. The PRISMA method has been followed to select the publications, identifying 15 documents to analyze. The results show that some groups of teachers from different educational levels are interested in mediating their math classes with digital games. The areas where digital games are mostly incorporated are arithmetic, geometry, and algebra, with a greater presence of serious games than commercial ones.